Spectral approach to white noise analysis - Berezansky, Yu. M.; Livinskii, V. O.; Lytvynov, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using the spectral projection theorem, we construct the classical Segal transformation as a Fourier transformation in the generalized joint eigenvectors of a certain family of field operators. It is noted that the spectral approach to the Segal transformation, which forms the basis of the analysis of Gaussian white noise, enables one to construct a significant generalization of this transformation.